Caesarean section: a journey not always smooth: complications of caesarean section - Kumar, Mukesh; Sharma, Rohini; Shah, Ravi; Abhishake, Bharti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Caesarean section (CS) is one of the most commonly performed obstetric procedures worldwide, with rates rising significantly over the past decades. While lifesaving, CS is associated with a spectrum of maternal and neonatal complications. Maternal risks include hemorrhage, uterocervical lacerations, urinary tract injury, postpartum infections, venous thromboembolism (VTE), chronic pelvic pain, uterine rupture, placenta previa, placenta accreta spectrum, caesarean scar ectopic pregnancy, caesarean scar niche, endometriosis, secondary infertility, and acquired uterine arteriovenous malformations (AVMs). Neonatal complications include superficial injuries, cephalhematoma, fractures, nerve injuries, lower Apgar scores, respiratory distress, increased NICU admissions, and long-term risks of asthma, obesity, and immune-related disorders. The increasing prevalence of CS underscores the importance of understanding its short-and long-term impacts on maternal and child health, emphasizing the need for careful risk assessment, preventive strategies, and informed clinical management.